Geometric Design of the Panjalin-Palasah Road in Majalengka Regency - Mochamad Chaical; Iman Gunawan; Chandra Wijaya Iko Saputra; Herry Hermawan (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Indonesia's transportation infrastructure faces challenges due to rapid urbanization and economic growth, especially in Majalengka. To address this, alternative road planning on the Panjalin–Palasah road in Majalengka Regency aims to improve vehicle flow. This study designs an optimal geometric road alignment following Indonesian Road Geometric Design Guidelines (PDGJI 2021) and evaluates route efficiency. The methodology combines quantitative and qualitative approaches using field surveys and secondary data. Geometric road planning focuses on the physical design to ensure the road performs its main function: facilitating smooth traffic flow. The analysis identified Route 2 as optimal, with a length of 6.1 km and an average gradient of 1.9%. Horizontally, the route features Spiral–Circle–Spiral (S-C-S) bends with three such corners. Vertically, the alignment includes two curve types, convex and concave. The excavation volume is 1,642.22 m³, fill volume is 2,190.61 m³, yielding a remaining volume of 548.39 m³. This road design offers a technically feasible and economically efficient solution to improve regional connectivity and support local economic growth in Majalengka Regency.